Synthesis of CaOZnO Nanoparticles Catalyst and Its Application in Transesterification of Refined Palm Oil - Cicik Herlina Yulianti; Ratna Ediati; Djoko Hartanto; Tri Esti Purbaningtias; Yoshifumi Chisaki; Aishah Abdul Jalil; Che Ku Nor Liana Che Ku Hitam; Didik Prasetyoko (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
The CaOZnO nanoparticle catalysts with Ca to Zn atomic ratios of 0.08 and 0.25 have been successfully synthesized by co-precipitation method. The catalyst was characterized by X-ray Diffraction (XRD) analysis provided with Rietica and Maud software, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared spectroscopy (FT-IR), and its properties was compared with bare CaO and ZnO catalysts. The phase composition estimated by Rietica software revealed that the CaO catalyst consists of CaO and CaCO3 phases. The estimation of the particle size by Maud software, showed that the particle size of all catalysts increased by the following order: ZnO. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)